Construction and comparison of the efficiency of different selection indices for malabari goats - Rani Alex (Department of Animal Breeding, Genetics and Biostatistics, College of Veterinary and Animal Sciences, 2009)
The study was conducted with the objective of optimizing the genetic improvement of Malabari goat population in North Kerala by adopting an index method of selection incorporating various growth traits and peak yield of dam. Present study was undertaken on 1055 records of animals born from August 2005 to August 2008 from the farmers’ flocks of AICRP on goats for Malabari goats.